2022
DOI: 10.1080/09603409.2022.2058228
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on the modelling of the minimum creep strain rate and the creep cavitation damage and fracture

Abstract: Modelling of the long-term creep damage and lifetime is very challenging, because the minimum creep strain rate, the lifetime, and creep strain at failure are strongly stress level dependent.With the aim for developing a set of creep damage constitutive equations for high Cr steel suitable for long-term service, research work was carried out in the modelling of the minimum creep strain rate with a wide stress level, the modelling of creep cavitation damage and rupture, and the coupling between creep cavitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The research presented is one of the initial explorations of the practical implementation and applicability of the cavitated volume fraction (݂ ௩ ) as a creep damage indicative parameter. It further expands the application of the original idea [15] of using accurate and comprehensive cavitation data to develop the cavitation model and rupture model [10,13] and contributes to the creep damage lifetime prediction methodology [12]. This approach is based on creep cavitation data with strong scientific bases.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The research presented is one of the initial explorations of the practical implementation and applicability of the cavitated volume fraction (݂ ௩ ) as a creep damage indicative parameter. It further expands the application of the original idea [15] of using accurate and comprehensive cavitation data to develop the cavitation model and rupture model [10,13] and contributes to the creep damage lifetime prediction methodology [12]. This approach is based on creep cavitation data with strong scientific bases.…”
Section: Discussionmentioning
confidence: 92%
“…Creep deformation and fracture time predictions have mainly been characterised using the continuum damage mechanics (CDM) [3][4][5][6]; empirical models that depend on parameterizing the creep curve [7][8][9] and direct cavitation damage models [10][11][12][13]. It is well known that an accurate description of the creep deformation and lifetime is still a contemporary problem in material science and in structural integrity research.…”
Section: Introductionmentioning
confidence: 99%
“…This would suggest the need for incorporating partial coalescence effects into the model to enhance its predictive accuracy [26] Background on the current cavitation model (Riedel's Cavitation Model) Cavity nucleation rate has been traditionally associated with the creep strain rate (phenomenological approach) but Qiang has pointed out its inaccuracy in the application of such approach originally; [27] then in [28]. This had motivated research to pursue the stress driven cavity nucleation research; though this is not the mainstream of research activities reported in literature, but it is the right direction to take; It is also expected that the stress driven approach due to its mechanism based, rather than the phenomenological approach, would give better chance to extrapolate as proposed and evidenced by Xu [29].…”
Section: Problem Overviewmentioning
confidence: 99%